PROFIL PENGKAJIAN RESEP RACIKAN PASIEN RAWAT JALAN DI INSTALASI FARMASI (RSUD) PRATAMA IBU KOTA NUSANTARA - Kurnia Arinar Pramentari; Nurlina Nurlina; A. Hasrawati (Nusantara Hasana Journal, 2026)
Prescription assessment is a critical component of pharmaceutical services, ensuring patient safety, treatment effectiveness, and the appropriateness of drug therapy. This study analyzed the profile of compounded prescriptions for outpatients at the Pharmacy Installation of Pratama Regional Hospital, Nusantara Capital City, and evaluated their compliance with administrative, pharmaceutical, and clinical standards as outlined in the Indonesian Ministry of Health Regulation No. 72 of 2016 on Hospital Pharmaceutical Services. Using a descriptive, non-experimental retrospective approach, the findings revealed persistent inconsistencies across all aspects assessed. Between July and December 2024, administrative completeness was achieved only for patient name, prescription date, and physician’s address (100%), while pharmaceutical completeness for drug name, dosage form, and usage instructions also reached 100%; however, dosage and drug quantity remained inadequate. Clinically, dosage accuracy was 66.7%, with 21.5% overdoses, 5.5% exceeding the usual dose, and 6.3% underdosing. No duplication of drugs was identified, and no major drug interactions were observed, though moderate interactions occurred in certain combinations. These results underscore the need for strengthened supervision and prescriber education to improve adherence to pharmaceutical service standards, thereby enhancing patient safety and optimizing therapeutic outcomes.